Acquired latent tuberculosis infection in psoriasis patients treated with etanercept in the People’s Republic of China - Li CR; Mao QX; Chen M; Jia WX; Yao X; Feng SY; Jia H; Gong JQ; Yang XY (Dove Medical Press, 2015)
Cheng-Rang Li, Qiu-Xia Mao, Min Chen, Wei-Xue Jia, Xu Yao, Su-Ying Feng, Hong Jia, Juan-Qin Gong, Xue-Yuan Yang Institute of Dermatology, Chinese Academy of Medical Sciences & Peking Union Medical College, Nanjing, Jiangsu, People’s Republic of China Background: TNF-α plays a key role in host defense against mycobacterial infection, and patients receiving TNF-α blocker treatment have increased susceptibility to tuberculosis disease. In the People’s Republic of China, an intermediate tuberculosis-burden country, the latent tuberculosis infection (LTBI) risk in patients with psoriasis who are treated with etanercept, the safest kind of TNF-α blocker, is unknown.Objectives: This study reports the LTBI risk in patients with psoriasis after etanercept treatment and aims to answer the question of how often rescreening for LTBI should be done in order to reduce active tuberculosis infection of patients and further reduce the incidence of active tuberculosis disease.Patients and methods: This retrospective review evaluated patients with moderate-to-severe chronic plaque psoriasis between 2009 and 2013. All patients were excluded tuberculosis infection and received etanercept 25 mg twice weekly, then the patients were checked for LTBI 3 months after etanercept treatment to observe the incidence of LTBI and assess the need for rescreening for LTBI every 3 months.Results: We retrospectively analyzed 192 patients with psoriasis with moderate-to-severe chronic plaque whose tuberculin skin test and chest X-rays were negative and who received etanercept 25 mg twice weekly. Eighteen of them were excluded because they received less than 3 months of etanercept therapy. After treatment with etanercept, four patients were found to have LTBI.Conclusion: In this study, the incidence of LTBI after 3 months was four in 192 (2.1%), which is higher than the annual incidence of LTBI in the People’s Republic of China (0.72%), so LTBI could be expected to occur within 3 months in psoriasis patients on etanercept. Periodic screening for LTBI in the therapy course, as well as before initiating treatment, is necessary in those patients who use a TNF-α blocker. We recommend rescreening for LTBI every 3 months. Keywords: TNF receptor, TNFR, fusion protein, treatment, LTBI, TB screening